KAJIAN EFEKTIFITAS PEMBERIAN PUPUK GUANO DAN BIOCHAR TERHADAP PRODUKSI DAN SERAPAN HARA NPK TANAMAN PADI - Bustami Bustami; Elvrida Rosa (Jurnal Agrotek Lestari, 2018)
This research was conducted to examine the effect of dosage of guano and biochar fertilizer on the production and absorption of N, P and K nutrients. The implementation of the research was done in Laboratory of Kasa Faculty of Agriculture, University of Abulyatama, Aceh Besar and analysis of N, P and K absorption of rice plant was carried out in Laboratory Soil Chemistry University Syiah Kuala Banda Aceh. This study used a Completely Randomized Design Plan (RAL) with three replications. The treatment consisted of dosage of Guano fertilizer 4 levels (0 kg / ha, 5 tons / ha, 10 tons / ha and 15 tons / ha and Biochar 3 levels (0 tons / ha, 5 tons / ha and 10 tons / ha). was done on plant height, number of tiller, dry weight, weight of grain per plant, weight of 1000 grain, empty grain weight and nutrient uptake of N, P and K. The dosage of Guano (G) fertilizer had a very significant effect on plant height and number of tillers aged 15 HST, significant effect on plant height of 60 HST and significant effect on plant height age 30 and 45 HST, number of tillers 30, 45 and 60 HST and weight of grain per plant Biochar dose very significant effect on plant height and number of tillers aged 15 HST, significantly affected the age of 60 HST and had no significant effect on plant height aged 30 and 45 HST, number of tillers 30, 45 and 60 HST and weight of grain per plant There was a significant interaction between the dosage of Guano and Biochar fertilizer on the number of tillers 60 HST. Keywords: guano, biochar, nutrient uptake